Development of nitrifying biofilm for wastewater treatment - Tay, Joo Hwa (2008)
With increasing demands on water quality, advanced and cost effective techniques for nitrogen removal fiom wastewater become more and more important and it is believed that biological nitrification-denitrification is an economical method for nitrogen removal. Nitrifying biofilm is such an effective system for nitrogen removal. Thus, this study focused on the growth kinetics of nitrifying biofilm and nitrite build-up in nitrifying biofilm reactor.